Toxic effect of Annona muricata seed extracts potentiated with dimethyl sulfoxide on IV larvae and pupae of Aedes aegypti - Bobadilla Alvarez, Miguel Constante (2020)
The objective of this study was to demonstrate that active ingredients of Annona muricata seeds can be enhanced as a result of mixture of both ethanolic extract of A. muricata seeds and Dimethylsulfoxide (EE-DMSO). Percentage mortalities at 6, 12, 24 and 48 hours on fourth instar larvae and pupae of Aedes aegypti were calculated in order to compare bioactivities of aqueous (AE), ethanolic extracts (EE) and EE-DMSO under laboratory and simulated field conditions. Results showed larval mortality concentration- and time-dependent, and knock-down responses in pupae. In laboratory, AE and EE exerted 100% larval mortality at 5 mg.L-1 after 24 hours (LC50= 46.16 and 19.28 mg.L-1). Conversely, EE-DMSO showed between 62 – 100% mortality at 0.5 mg.L-1 for over 6 hours (LC50= 20.33 mg.L-1). Pupicidal effects in AE and EE revealed 100% mortality at 24 hours employing all concentrations, except in EE-DMSO which commenced when individuals were exposed between 6 and 12 hours. In simulated field, AE and EE provoked 100% larval mortality at 24 hours (16.91 y 21.21 mg.L-1) while pupal mortality at 12 hours (20.44 y 23.03 mg.L-1). Percentage mortality of pupae was 100% using EE-DMSO even before 6 hours. Comparative toxic effects of laboratory and simulated-field systems have shown to maintain a similar pattern of larval mortality and more sensitive responses in pupae. Accordingly, larval and pupal mortality responses of A. aegypti were enhanced with the use of EE-DMSO and active ingredients of A. muricata seeds under laboratory and simulated field conditions.